Does votong history matter? Analysing persistence in turnout - Kevin Denny; Orla Doyle (University College Dublin, UCD School of Economics, 2006)
Individuals who vote in one election are also more likely to vote in the next. Modelling the causal relationship between past and current voting decisions however is intrinsically difficult, as this positive association can exist due to habit formation or unobserved heterogeneity. This paper overcomes this problem using longitudinal data from the British National Child Development Study (NCDS) to examine voter turnout across three elections. It distinguishes between unobserved heterogeneity caused by fixed individual characteristics and the initial conditions problem, which occurs when voting behaviour in a previous, but unobserved, period influences current voting behaviour. It finds that controlling for fixed effects unobserved heterogeneity has little impact on the estimated degree of habit in voter turnout, however failing to control for initial conditions reduces the estimate by a half. The results imply that voting in one election increases the probability of voting in a subsequent election by 13%.
hdl:10197/951
Keywords: 330; Voter turnout; habit formation; dynamic panel models